Species-specific interactions between Marrubium vulgare solvent extracts and entomopathogenic nematodes for Phthorimaea operculella (Lepidoptera: Gelechiidae) control - Davoud Mohammadi; Albrecht M. Koppenhöfer; Naser Eivazian Kary (BioControl, 2026)

A new potential biological control agent—the interaction between the parasitoid fly Neobrachelia edessae (Diptera: Tachinidae) and the stink bug Edessa meditabunda (Hemiptera: Pentatomidae) - María Candela Barakat; Sofía Pilar Díaz; Rodrigo de Vilhena Perez Dios; Graciela Minardi; María Fernanda Cingolani (BioControl, 2026)
Tachinid flies are natural enemies of adult hemipterans of the family Pentatomidae, which are considered pests of economically important crops. We evaluated the performance of Neobrachelia edessae Townsend (Diptera: Tachinidae), a Neotropical parasitoid fly of the stink bug Edessa meditabunda (Fab.) (Hemiptera: Pentatomidae), and assessed the effects of parasitism on host longevity, fecundity, and fertility. Differences in parasitism rates were analysed considering host exposure times, number of male parasitoids per experimental unit, maternal origin of the female fly, and sex of the offered host. In addition, the performance of the F1 generation was evaluated in terms of parasitism success. Female performance improved with longer host exposure times, when female parasitoids had copulated with more than one male, and when female flies were obtained from field-collected hosts. More than 60% of the progeny from the parasitoid females that were allowed to copulate with more than one male were able to pupate, whereas when parasitoid females copulated with only one male, just 44% of the progeny were able to pupate. Parasitism decreases the longevity of both male and female hosts and reduced both the fecundity and fertility of females. Moreover, parasitized E. meditabunda exhibited lifespans of approximately half those of unparasitized stink bugs. In addition, parasitized females experienced an approximate 30% decline in fecundity and a 23% decline in fertility relative to unparasitized females. These results indicate that N. edessae has a strong potential as a biological control agent of E. meditabunda .

Flowering plants mediate stronger top-down pest regulation in maize fields - Mihwan Sataral; Akhmad Rizali; I. Wayan Winasa; Hermanu Triwidodo; Rosyid Amrulloh; Fajrin Fahmi; Damayanti Buchori (BioControl, 2026)

Virulence and transmission potential of indigenous entomopathogenic fungi against Halyomorpha halys (Stål) (Hemiptera: Pentatomidae) - Zeynep Bayramoğlu; Merve Ayşe Doğancı; Bora Öktem; Hatice Çolak; Ardahan Eski; Seda Biryol; İslam Saruhan; İsmail Demir (BioControl, 2026)

Molecular and functional analysis of RNAi machinery genes in a neuropteran insect predator, Chrysoperla zastrowi sillemi - V. S. Chinnu; M. Mohan; R. Manjunatha; P. J. Aneesha; Suresh R. Jambagi (BioControl, 2026)

spp.as biocontrol agents of post-harvest fungal decay in fruits and vegetables: mechanisms of action, challenges and opportunities - Leidoh Marcellin Akpafi; Wenwen He; Guanghao Li; Chenyang Zhu; Mengyue Wu; Yun Wang (BioControl, 2026)

Can biological control become a scalable solution for crop pest management in Nigeria? A focus on entomopathogenic nematodes - Christopher Tobe Okolo; Christian Borgemeister (BioControl, 2026)
The over-reliance on chemical pesticides for crop pest control has raised serious concerns about their environmental and health impacts. Biological control agents (BCAs), including entomopathogenic nematodes (EPNs), offer safer and more sustainable alternatives. Despite promising experimental results, adoption of BCAs in sub-Saharan Africa remains limited. In Nigeria, EPNs are largely unknown to farmers, and no commercial production or importation system exists. This study investigates the sociocultural and institutional factors influencing farmers’ willingness to adopt EPNs as a biological control strategy. We surveyed 740 smallholder farmers across ten study locations (two per agroecological zone; n = 74 farmers per location) representing five major agroecological zones of Nigeria. The survey was done from May to August 2022. Awareness of EPNs was virtually absent across all locations (mean

Intraguild predation and biological control: developing a new model to evaluate parasitoid-predator interactions - María B. Aguirre; Octavio A. Bruzzone; Serguei Triapitsyn; Stephen Hight; Hilda Diaz-Soltero; Guillermo A. Logarzo (BioControl, 2026)

Biocontrol potential of anthracnose in sorghum by Bacillus spp. and its lipopeptide extracts - Nataniel Osmar Risse; Evilyn Eduarda Prandini Santana; Vinicius Facin Nugoli; Fernanda Koch; Marco Antonio Bacellar Barreiros; Luciana Grange; Vivian Carré Missio; Robson Fernando Missio (BioControl, 2026)
Climate change is increasing constraints on crop production and reinforcing the need for sustainable alternatives to chemical disease control. Sorghum is a drought-tolerant crop of increasing importance. However, anthracnose caused by Colletotrichum sublineola remains its most destructive disease, and no biological control products are currently registered for its management. This study evaluated bacterial isolates as potential biological control agents against sorghum anthracnose. Bacteria isolated from honey were identified as Bacillus spp. based on 16S rDNA sequencing and screened for antifungal activity in vitro . Four isolates inhibited mycelial growth of C. sublineola by more than 67%. Lipopeptide extraction and characterization confirmed the production of surfactin, fengycin, and iturin. Greenhouse assays demonstrated that bacterial cell suspensions reduced symptomatic leaf area by 40%, whereas lipopeptide extracts reduced disease severity by 77% and significantly increased the chlorophyll index. The most effective treatments were further evaluated under field conditions, confirming their effects on disease suppression and plant physiological performance. Three Bacillus isolates showed strong potential for biological control of sorghum anthracnose using both talc-based formulations and lipopeptide extracts. Further studies are required to optimize formulation stability and assess long-term field efficacy.

Vip3Aa35 enhances the efficacy of Bacillus thuringiensis, Beauveria bassiana, and SeNPV for Spodoptera exigua control: a synergistic approach for sustainable pest management - Mongkon Utamatho; Sumarin Soonsnga; Cheerapha Panyasiri; Amporn Rungrod; Samrit Kiewwong; Boonhiang Promdonkoy (BioControl, 2026)

Efficacy of an indigenous entomopathogenic fungus, Aschersonia aleyrodis, in controlling Bemisia tabaci on soybean - Marida Santi Yudha Ika Bayu; Yusmani Prayogo; Sri Wahyuni Indiati; Apri Sulistyo; Alfi Inayati; Dewi Rumbaina Mustikawati; Gatut Wahyu Anggoro Susanto; I Nyoman Widiarta; Yadi Suryadi; Trizelia; Otto Endarto; Arief Harsono; et al. (BioControl, 2026)
Bemisia tabaci (Gennadius) is a major pest in soybean, causing both direct feeding damage and acting as a vector for several plant viruses. The emergence of resistant B. tabaci biotypes to synthetic insecticides underscores the need for effective and sustainable alternatives. This study evaluated the efficacy of an indigenous isolate of the entomopathogenic fungus (EPF) Aschersonia aleyrodis (TMP-Dc3) for managing B. tabaci populations under laboratory and field conditions between February and October 2024. Treatments included varying conidial concentrations of A. aleyrodis (10 5 , 10 6 , 10 7 , and 10 8 conidia ml −1 ) and a synthetic insecticide (thiamethoxam) as a chemical control. The 10 7 conidia ml −1 treatment significantly suppressed B. tabaci populations in the field compared to other fungal densities and thiamethoxam. Notably, B. tabaci densities were higher in the thiamethoxam treatment, likely due to reduction in natural enemy abundance. Although thiamethoxam-treated plants produced slightly higher seed yields (14.26 g plant −1 ), plants treated with 10 7 conidia ml −1 of A. aleyrodis achieved a comparable yield (14.03 g plant −1 ). A significant negative correlation was observed between the number of empty pods and total seed weight (r = –0.697), while a positive correlation existed between whitefly populations at 56 days after planting and empty pods (r = 0.476). The TMP-Dc3 isolate exhibited strong chitinase and protease activities, highlighting its potential as a promising biopesticide and sustainable alternative to chemical insecticides for managing B. tabaci in soybeans crops.

Efficacy of new biocontrol agents against Rhizoctonia solani in lettuce evaluated through an automated imaging system and their effect on bacterial soil communities - Alessia Follador; Marco Torrente; Stefano Morandi; Paolo Tirelli; Matteo Gualandris; Alessandro Passera; Abdeslam Asehraou; Milena Brasca; Roberto Oberti; Paola Casati (BioControl, 2026)
In recent years, biocontrol agents (BCAs) have gained attention as sustainable alternatives or complements to synthetic chemicals for managing phytopathogens and enhancing plant growth. In this study, six bacterial strains were evaluated as BCAs against Rhizoctonia solani (RS), a soil-borne pathogen affecting economically important crops. Two strains ( Bacillus sp. B04A33 and Psychrobacillus sp. B04A42) were isolated from maize embryos, while Lactiplantibacillus plantarum strains (ITEM 17215, ITEM 17218, ITEM 18335 and S61) originated from food or animal sources. A commercial Trichoderma -based product (REMEDIER®, Gowan Italia) served as the control. Biocontrol effectiveness was assessed both in vitro and in vivo on lettuce using an automated imaging system for plant growth monitoring. In soils infected by R. solani, the inoculum of s trains B04A33, B04A42, and S61 enhanced germination and seedling vigor, and increased dry weight of shoots and roots. Root system development, analyzed via image processing in Matlab, confirmed improved growth. The qPCR analysis of soil samples showed that microbial abundance increased in non-treated (NT) and S61 + RS treatments, while R. solani levels decreased in B04A33 + RS and B04A42 + RS. Oxford Nanopore MinION sequencing of soil samples revealed dominance of Pseudomonadota , Actinomycetota , and Bacillota , with enrichment of Bacillaceae and Lactobacillaceae in B04A42 and S61 treatments, confirming the successful establishment of the inoculated strains within the soil microbiome. These results support both the potential of selected bacterial strains as effective BCAs against RS and the use of automated imaging in BCAs screening procedures, promoting sustainable and technology-assisted crop management.

Evaluation of the predatory soil mite Blattisocius mali (Acari: Blattisociidae) as a biocontrol agent of the acarid mite Tyrophagus putrescentiae (Acari: Acaridae) infesting stored flower bulbs - Manoj Kumar Jena; Marcin Studnicki; Dariusz Sochacki; Katarzyna Michalska (BioControl, 2026)

Trade-offs between regeneration and development under food stress in the biocontrol agent, Cheilomenes sexmaculata (Coleoptera: Coccinellidae) - Shriza Rai; Tripti Yadav; Geetanjali Mishra (BioControl, 2026)

Harnessing phage biocontrol strategies for managing bacterial plant pathogens - Sajad Ali; Tarequl Islam; Mohammed A Almalki; Muhammad Fazle Rabbee (BioControl, 2026)

Developmental morphology reveals the key parasitic role of the first-instar larva in the hypermetamorphosis of Dastarcus helophoroides (Coleoptera: Bothrideridae) - Yifan Zhang; Ke Wei; Xueting Yang; Cuicui Geng; Shangkun Gao (BioControl, 2026)

Genomic insights and biocontrol potential of endophytic Bacillus subtilis strain B_SP against fungal pathogen Colletotrichum gloeosporioides in Dioscorea alata L. - Amrutha Pandirikkal Ravindran; Jeeva Muthulekshmi Lajapathy; Sreelatha Gopalakrishnan Lalithakumari; Makeshkumar Thangaraj; Veena Syamala Swayamvaran; Tom Cyriac; Akhil Kannolickal Mohan; Shilpa Sreekumar Usha (BioControl, 2026)

Selectivity of few chemical insecticides and entomopathogenic fungi Cordyceps fumosorosea on the parasitoid Encarsia guadeloupae and on the predator Apertochrysa astur in coconut - Rakshith H.S; Jayalaxmi Narayan Hegde; Sumalatha B.V; Selvaraj K; Rajashekarappa K; Ganesha Naik R; Thippesha D (BioControl, 2026)

Identification and fumigant effects of nematicidal volatile organic compounds produced by nematophagous fungi against root-knot nematodes - Cássia Gondim Pereira; Jodieh Oliveira Santana Varejão; Aline Ferreira Barros; Walysson Ferreira de Paiva; Huarlen Márcio Balbino; Dyenici Rodrigues; Maria Eliana Lopes Ribeiro de Queiroz; Leandro Grassi de Freitas; Eduardo Vinícius Vieira Varejão (BioControl, 2026)
Plant-parasitic nematodes of the genus Meloidogyne , commonly known as root-knot nematodes, pose a significant threat to global agricultural productivity. Due to concerns about environmental impact and human health risks, the use of commercially available synthetic nematicides has become increasingly restricted. Consequently, the search for natural molecules with nematicidal properties has emerged as a promising alternative. In this study, we found that nine nematophagous fungal isolates belonging to the genera Arthrobotrys , Monacrosporium , Duddingtonia , and Pochonia produce volatile organic compounds (VOCs) with nematicidal activity against Meloidogyne incognita . The major VOCs, identified by SPME–GC–MS, exhibited high mortality rates against second-stage juveniles (J2) of M. incognita , with LC₅₀ values comparable to, and LC₉₅ values lower than, those of the commercial nematicide fluensulfone. All identified VOCs significantly inhibited egg hatching in vitro, and several compounds, at concentrations of 200 μg ml⁻ 1 , nearly eliminated in vivo nematode reproduction in soybean plants under fumigation assays. Among them, 1-octen-3-ol, 3-octanone, and benzaldehyde showed the greatest potential as natural bionematicidal fumigants. This is the first report of nematicidal VOC production by A. cladodes , A. conoides , A. robusta , A. musiformis , and M. thaumasium .

Correction to: Effects of microhabitats and seasonal conditions on the supercooling points of Tetrastichus planipennisi (Hymenoptera: Eulophidae) in Vermont, USA - George Ni; Nicholas J. Gotelli; Jian J. Duan (BioControl, 2026)

Effects of microhabitats and seasonal conditions on the supercooling points of Tetrastichus planipennisi (Hymenoptera: Eulophidae) in Vermont, USA - George Ni; Nicholas J. Gotelli; Jian J. Duan (BioControl, 2026)

Idiobiont or koinobiont? Re-evaluating the parasitism mode of Aphytis sp. nov., a biological control agent of San Jose scale - Paula Altesor; Álvaro García; Marianela Larramendy; Irene Pandulli (BioControl, 2026)

Intercropping Brassica rapa with soybean suppresses Myzus persicae population growth and increases attraction of adult Harmonia axyridis - Xixian Chen; Zihao He; Xu Yanbo; Jamin Ali; Adil Tonğa (BioControl, 2026)

Divergent immune responses of Phytoseiid mites to bacterial pathogen Acaricomes phytoseiuli - Hong Yan; Yu Chen; Xiangli Dang; Endong Wang; Xuenong Xu; Bo Zhang (BioControl, 2026)

Diet-driven reproduction: exploring the relationship between aphid feeding and fertility in the lady beetle Eriopis connexa (Coleoptera: Coccinellidae) - Caio Victor de Brito Remigio; Ianne Caroline da Silva Nobre; Glaucilane S. Cruz; Jorge Braz Torres; Valéria Wanderley Teixeira; José Dijair Antonino (BioControl, 2026)
Eriopis connexa , a neotropical aphidophagous lady beetle important for various soft-bodied pest species control, requires feeding on aphids for enhanced reproductive output. To understand the physiological basis of this dependency, we investigated how the absence of the preferred prey, aphids, affects E. connexa reproductive fitness. We compared females fed only Ephestia kuehniella eggs (a factitious food) with those provided E. kuehniella eggs alongside limited access to the aphid Lipaphis pseudobrassicae (a preferred prey). Egg numbers were similar in females from both diets after 60 days. However, females on an aphid-supplemented diet cease oviposition around day 30, exhibiting egg viability around 35%. Conversely, females fed with E. kuehniella eggs alone cease oviposition around day 60, with egg viability close to 0. These females also exhibited greater longevity. At the molecular level, the lack of aphids resulted in females with a ~twofold downregulation of Vitellogenin 1 ( Vg1 ) and a dramatic ~40-fold upregulation of its receptor, VgR . Key genes in the insulin signaling pathway ( AKT and FoxO ) were also upregulated. Biochemically, the aphid-free diet led to females with higher glycogen levels, supported by the upregulation of Glycogen Synthase ( GS ). Therefore, the absence of aphids in E. connexa diet led to altered egg-laying pattern, reduced fertility and longer lifespan. This physiological shift, mediated by the insulin pathway and glycogen levels, highlights how preferred prey regulates reproductive success. These findings provide a basis for optimizing mass-rearing protocols, allowing for more cost/labor-effective maintenance of E. connexa in biological control programs.

Development of dry and oil-based formulations of Metarhizium anisopliae using carrier materials for effective control of red flour beetle, Tribolium castaneum (Coleoptera: Tenebrionidae) - Nahdia Perveen; Abu Bakar Muhammad Raza; Muhammad Arshad; Panagiotis Eliopoulos; Samah F. Ibrahim; Mustafa Shukry; Samy Sayed; Hanan M. A. Hamada (BioControl, 2026)

Intrinsic competition between Coptera haywardi (Hymenoptera: Diapriidae) and two native opiine parasitoid species attacking Anastrepha ludens (Diptera: Tephritidae) immatures - Gibran Clemente; Jorge Toledo; Gabriela Pérez-Lachaud; Salvador Flores; Javier Valle-Mora; Pablo Liedo; Pablo Montoya (BioControl, 2026)

Development of a multiplex PCR assay to identify two key alfalfa weevil (Hypera postica) parasitoids, Bathyplectes curculionis and Oomyzus incertus, in western North America - Chulantha P. Diyes; Michelle Reid; Priyanka Mittapelly; Jennifer Holowachuk; Julian R. Dupuis; Héctor A. Cárcamo; Boyd A. Mori (BioControl, 2026)

A classical biological control program revisited: establishment, spread and mitochondrial diversity of Neodusmetia sangwani (Subba Rao) (Hymenoptera: Encyrtidae) - Chrysalyn Dominguez; Jessica Simons; Iris Chien; John M. Heraty (BioControl, 2026)
Neodusmetia sangwani (Subba Rao) (Encyrtidae) is a classical biological control agent of the rhodesgrass mealybug, Antonina graminis (Maskell) (Pseudococcidae), imported from India and first released in Texas, USA in 1959. Although subsequent releases were considered established in Arizona and Hawai`i, USA, establishment in California following releases in the Imperial Valley in 1968 had not been confirmed. Yellow pan trap surveys conducted on the University of California, Riverside campus, USA in 2016, 2024, and 2025 yielded more than 150 specimens across multiple habitats, with additional collections from Jurupa Valley and community science records (iNaturalist) from San Diego, California, supporting the presence of persistent populations. These findings document the successful establishment and year-round persistence of N. sangwani in southern California, USA. Mitochondrial cytochrome c oxidase I (COI) barcodes were generated for California specimens and compared with records in the Barcode of Life Database (BOLD) and the Global Biodiversity Information Facility (GBIF). Fifty closely matching sequences were identified worldwide, representing four geographically structured Barcode Index Numbers (BINs) of N. sangwani from Africa, South Asia, Australia, and the Americas. Mean mitochondrial divergence among BIN-associated clades ranged from 2.5–5.3% (Kimura 2-parameter), with the greatest differentiation observed in specimens from India and Pakistan. Despite this mitochondrial structure, no consistent morphological differences were detected among lineages. iNaturalist observations document a much broader global distribution. Our results confirm the establishment of N. sangwani in California and highlight the value of combining DNA barcoding with global biodiversity databases to improve post-release monitoring and assess lineage-level genetic variation in biological control agents.

Control of fall armyworm with Spodoptera frugiperda multiple nucleopolyhedrovirus in sweet corn cultivated under agroecological conditions - T. Cunningham; C. de la Colina; M. Pérez; G. Quintana; Marco D´Amico; M. Berretta; J. Niz; M. L. Ferrelli; R. Salvador (BioControl, 2026)

Novel lactic acid bacteria as biocontrol agents against tomato bacterial canker: genomic insights into biosynthetic gene clusters - Hande Evren Arda Ergin; Utku Sanver; Hatice Ozaktan (BioControl, 2026)
Bacterial canker, caused by Clavibacter michiganensis subsp . michiganensis , remains one of the most devastating diseases affecting tomato production globally, necessitating sustainable biocontrol strategies. This study investigates the biocontrol potential and plant growth efficacy of indigenous lactic acid bacteria isolated from tomato tissues in the Izmir province of Türkiye. Six potent isolates, identified as Lacticaseibacillus paracasei and Lacticaseibacillus zeae , were evaluated through in vitro assays and in planta trials across two susceptible tomato cultivars, ‘SC2121’ and ‘Corvette’. While the isolates exhibited no direct antagonism against Clavibacter michiganensis subsp . michiganensis in dual culture assays, they demonstrated significant disease suppression in planta , with Lacticaseibacillus paracasei LBT2 (G1) achieving up to 45.71% efficacy. All isolates displayed robust plant growth promoting traits, including indole acetic acid production, siderophore activity, and phosphate solubilization, leading to substantial increases in root and shoot biomass. To elucidate the molecular mechanisms underlying these effects, the whole genome of the most effective strain, LBT2, was sequenced. Genomic mining revealed five distinct biosynthetic gene clusters, including an arylpolyene cluster (88% similarity) for oxidative stress protection and an aerobactin-like siderophore cluster (66% similarity). Notably, the presence of highly divergent NRPS (3% similarity) and thiopeptide (14% similarity) clusters suggests the potential for novel, cryptic antimicrobial metabolites that may be activated within the host environment. These findings position Lacticaseibacillus paracasei LBT2 as a multi-functional biocontrol agent that integrates direct growth promotion with genomic potential for pathogen suppression, offering a promising tool for integrated pest management in tomato cultivation.

miR-8 modulates reproductive and tissue homeostasis traits in Arma chinensis Fallou: a new insight to improve biological control - Ximei Yuan; Yiqing He; Chen Wang; Yuejun Fu (BioControl, 2026)

Patch dispersal and parasitism efficiency of the parasitoid Telenomus podisi are influenced by host abundance and release accuracy - Nathália Graziele Falcão Fernandes; Júlio Alckmin Magalhães Souza; Pedro Vinicius Nogueira de Oliveira; Lessando Moreira Gontijo (BioControl, 2026)
Habitat quality is an important factor linked to decision-making in female parasitoids, whether related to the infestation patch quality or the availability of resources in the area. Host abundance, together with the spatial location of the infested patch, is known to be directly linked to the foraging time and parasitism efficiency of parasitoids. Within this context, this study aimed to investigate how host abundance affects patch residence time by Telenomus podisi (Hymenoptera: Scelionidae) and whether the accuracy of its spatial release in the field influences parasitism rates upon eggs of Euschistus heros (Hemiptera: Pentatomidae). Two separate experiments were conducted according to our objectives. The first, a microcosm experiment, evaluated the patch residence time in relation to host abundance. The second, a semi-field experiment, evaluated parasitism of E. heros eggs in relation to parasitoid release accuracy. The dispersal time of T. podisi females from the microcosm study was significantly lower at high densities of E. heros eggs. In addition, event probability analyses further indicated that females are less likely to disperse at high host egg abundance when compared to low abundance. In addition, the location where the parasitoids were released in the field had a significant effect on the parasitism rate. T. podisi parasitized more E. heros eggs when the females were released more accurately on the infestation spot. Given these results, host abundance and release accuracy should be considered to optimize the augmentative biological control of E. heros in soybean fields.

Survival of Metarhizium humberi in granular formulations, and activity against Aedes aegypti adults after prolonged storage - Juan Mercado Martinez; Juscelino Rodrigues; Ricardo Neves Marreto; Christian Luz (BioControl, 2026)
Interest in mycoinsecticides for integrated mosquito control is high, and a granular formulation of Metarhizium humberi is showing promising results against Aedes aegypti , a vector of important arboviruses in the tropics. Storage conditions will affect shelf-life and the further fitness of mycoinsecticides. Here, two granular formulations with microsclerotia plus conidia or with only conidia were packed loose or fixed on black cloth in bags with ambient or low air pressure and subsequently stored at 25 °C or 4 °C for up to 24 months. Temperature proved to be the most critical factor for extended shelf-life. Both conidia and microsclerotia quickly lost their viability in the first two months of storage at 25 °C. The lower temperature distinctly retarded the decline of viability of propagules and increased shelf-life and activity in A. aegypti adults up to 16 months. The packing method used did not affect shelf-life and enables more flexible use. Often unavoidable suboptimal temperatures remain a major challenge for extended storage of mycoinsecticides that needs to be addressed.

Predation of Pterostichus melanarius on cocoons of soybean gall midge, Resseliella maxima - Regina S. Stacke; Sarah C. von Gries; Arthur V. Ribeiro; Pheylan A. Anderson; Amelia R. I. Lindsey; Robert L. Koch (BioControl, 2026)
The soybean gall midge, Resseliella maxima Gagné (Diptera: Cecidomyiidae), feeds on soybean, Glycine max (L.) Merrill (Fabales: Fabaceae), causing significant injury and yield losses. Pterostichus melanarius Illiger (Coleoptera: Carabidae), a generalist predator introduced to North America, has been reported to prey on R. maxima larvae under laboratory conditions. Understanding the feeding preference of P. melanarius on different prey life stages is important to evaluate its role in the biological control of R. maxima . Three laboratory experiments were conducted to assess predatory behaviors. In a no-choice test, P. melanarius adults fed on both R. maxima free (i.e., not cocooned) larvae and cocooned larvae, showing significant differences in prey consumption between R. maxima developmental stages over time. A choice test revealed a preference of P. melanarius adults for free larvae over cocooned larvae within the first hour, although this preference was not significant after 24 h. In an experiment examining the effect of soil on predation rates, P. melanarius adults consumed larvae and cocooned pupae placed either without soil, on the soil surface, or at a 1 cm depth, and predation rates were influenced by prey stage and the presence and depth of soil. These findings indicate that P. melanarius adults can feed on cocooned life stages, but that the presence of soil may hinder predation.

Biocontrol practitioners’ perspectives on emerging genetic-based technologies for weed management - M. A. Rafter; N. Kumaran; D. R. Brookes; M. K. Reid; K. E. Bowers; A. J. McConnachie; M. Cristofaro; R. F. H. Sforza; B. Gooden; M. Hopper (BioControl, 2026)
Weed biocontrol researchers have been at the forefront of developing management solutions for invasive weeds for over 100 years and have a unique perspective to offer on the emerging field of genetic-based technologies such as gene drive and RNAi. As part of the XVI International Symposium on Biological Control of Weeds in May 2023 we conducted a focus group discussion workshop to explore biocontrol practitioners’ perspectives related to: (1) Genetic-based control technologies, and the factors influencing support (or not) for their application to weed management, especially weed biocontrol, (2) perceived opportunities to apply genetic-based control tools to enhance or complement weed biocontrol, focusing on whether/how genetic tools can be applied to fundamentally change the practice of weed biocontrol, and (3) genetic-based control in weed management and how it can operate within the Access and Benefit Sharing regulatory landscape. We analyse the perspectives of biocontrol scientists from the workshop and discuss the prospects and challenges of integrating novel genetic-based control tools with weed biocontrol.

Behavioral and electrophysiological responses of fall armyworm larval parasitoid Coccygidium luteum to maize and companion plant volatiles - Emmanuel Peter; Sevgan Subramanian; Abdullahi Yusuf; Samira A. Mohamed; Baldwyn Torto; Emily A. Martin; Amanuel Tamiru (BioControl, 2026)
Companion cropping and biological control are among the best agronomic practices recommended for ecologically sustainable management of the invasive fall armyworm (FAW), Spodoptera frugiperda J.E. Smith (Lepidoptera: Noctuidae). Companion plants may suppress the FAW population by repelling the pest, disrupting host-plant location and recruiting biocontrol agents such as parasitoids. These interactions are primarily mediated by plant-derived volatile organic compounds (VOCs). Understanding parasitoids’ responses to VOCs emitted by companion plants enables selection of suitable cultivars to enhance biological control and design appropriate intercropping systems for effective FAW management. This study investigated behavioral and electrophysiological responses of a key FAW larval parasitoid, Coccygidium luteum Brullé (Hymenoptera: Braconidae), to odors from maize and different companion crops used in maize-based intercropping systems. In an olfactometer bioassay, gravid C. luteum were attracted to volatiles from FAW-damaged maize and intact companion plants (sweet potato, beans, groundnut) compared to control, but not to intact maize or cassava. Interestingly, females of C. luteum were equally attracted to volatiles from intact companion plants and FAW-damaged maize in multiple-treatment assays, suggesting that certain VOCs emitted by both plants may have ecological relevance. Chemical and electrophysiological analyses identified several bioactive compounds in the companion plant volatiles, including ( E )-2-hexenal, (Z)-3-hexenyl acetate, nonanal, ( E )-β-ocimene, ( E )-4,8-dimethyl-1,3,7-nonatriene, decanal, ( E )-nerolidol, and ( E , E )-4,8,12-trimethyl-1,3,7,11-tridecatetraene, known to influence parasitoid foraging. These findings provide further insight into the companion plants-FAW-parasitoid interactions and support the development of effective, economical, and environmentally friendly FAW management strategies using companion cropping and biological control.

Biological control of Sclerotinia sclerotiorum and improvement of growth and anatomical features in infected Phaseolus vulgaris plants by three Trichoderma strains - Asmaa El-Nagar; Yasser S. A. Mazrou; Abeer H. Makhlouf; Mansour M. El-Fawy; Mohamed G. A. Hegazy; Ghoname M. Amer; Duaa M. H. Rezk; Shahinaz E. Ahmed; Mohamed K. Abou-Shlell (BioControl, 2026)

Spatial modulation of multi-fungal antagonism in integrated insect and pathogen biocontrol - Mustapha Touray (BioControl, 2026)

Biocontrol action of Cladosporium anthropophilum against the wheat powdery mildew fungus Blumeria graminis f. sp. tritici - Sujing Zhao; Ziyi Fan; Juncong Liu; Mo Zhu; Zongbo Qiu (BioControl, 2026)

Characterization of a cypovirus isolate in Noctuoidea pests: host range, and stressor interactions - Alini de Almeida; Andrews Alexander Fredéric Monvosin Fisch; Luis Janssen; Leonardo Assis da Silva; Maria Cristina Neves de Oliveira; Daniel Mendes Pereira Ardisson-Araújo; Bergmann Morais Ribeiro; Daniel R. Sosa-Gómez (BioControl, 2026)

Non-contact effects of the parasitoid Sclerodermus guani on its two cerambycid host species - Yu-jun Kong; Yong-hao Nan; Hui-quan Sun; Ke Wei; Jian-rong Wei (BioControl, 2026)

Biological control of Fusarium fujikuroi, cause of bakanae disease of rice (Oryza sativa L.), using antagonistic bacteria - Istiaq Ahmed; Gareth J. Norton; Stephen Woodward (BioControl, 2026)

Trichoderma asperellum Tric 33 as a broad spectrum biopesticide against multiple diseases of tea (Camellia sinensis (L.) O. Kuntze) - R. D. S. M. Gamlath; K. L. S. C. Gunawardana; D. G. N. P. Karunajeewa; N. Mahadevan; P. D. Senanayake; S. Rajapakse; G. D. Sinniah (BioControl, 2026)

Evaluation of talc-based formulation of native Beauveria bassiana for control of polyphagous and sucking pests of cotton and yield improvement - Shah Mohammad Naimul Islam; Md. Zahid Hasan Chowdhury; Md. Ashraful Haque; Milia Bente Momtaz; Razia Sultana (BioControl, 2026)

Organic management of cherry orchards favours most natural enemies and some phytophages - Manuel González-Núñez; César Paúl; Helen Mamani; Cristina Elvira Fernández; Ismael Sánchez-Ramos (BioControl, 2026)
Arthropods were sampled in organic and conventional cherry orchards over two growing seasons using pitfall traps, yellow sticky traps, and branch shaking. The data obtained from both production systems were compared using linear mixed effects models and principal response curves (PRCs). The diversity of families and the total abundance of arthropods captured by the three sampling methods were significantly greater in the organic orchards. Phytophagous and predatory arthropods in cherry tree canopies, soil-dwelling predators and parasitoids captured in yellow sticky traps were significantly more abundant in organic orchards. Although no significant differences in the total abundance of Coccinellidae between crop managements were recorded, species richness and abundance, excluding that of Stethorus pusillus (Herbst) (Coleoptera: Coccinellidae), were significantly greater in the organic plots. According to the PRC analyses, the taxa most favoured by organic management were the predatory families Anthocoridae, Lycosidae, Staphylinidae, Gnaphosidae, Philodromidae, Hybotidae, Nabidae, Carabidae and Thomisidae; the parasitoids belonging to Pteromalidae, Mymaridae, Braconidae, Bethylidae, Platygastridae and Aphelinidae; and the phytophagous Monosteira unicostata (Mulsant & Rey) (Hemiptera: Tingidae) (poplar lace bug) and aphids. The predatory coccinellid species most favoured by organic cropping were Adalia decempunctata (L.) (Coleoptera: Coccinellidae), Adalia bipunctata (L.) (Coleoptera: Coccinellidae) and Scymnus interruptus (Goeze) (Coleoptera: Coccinellidae). In contrast, some groups of arthropods were more abundant in conventionally managed orchards, among which spider mites and their predatory species S. pusillus (Herbst) stood out. Therefore, this study revealed a great benefit of organic cherry cultivation for most groups of predators and parasitoids although some phytophagous species were also favoured.

Biocontrol of Sclerotinia sclerotiorum and plant growth promotion in common bean (Phaseolus vulgaris L.) by Bacillus spp. - Kássio de Marco; William Pietro-Souza (BioControl, 2026)
White mold, caused by Sclerotinia sclerotiorum , is one of the most important diseases affecting common bean crops. Due to its global distribution and wide host range, the persistence of S. sclerotiorum in the environment is favored by the formation of survival structures, which complicates control measures. In this context, biological control emerges as a sustainable strategy for pathogen suppression and plant growth promotion. To explore this approach, nine strains of Bacillus spp. were screened for their ability to control S. sclerotiorum strain SSF and promote growth of common bean ( Phaseolus vulgaris L.) plants. All strains exhibited antagonistic activity against S. sclerotiorum strain SSF, demonstrated through in vitro antagonism assays, including dual culture and cell-free supernatant (CFS) tests, and volatile organic compounds (VOCs) exposure, indicating the involvement of multiple antagonistic mechanisms. In addition, the strains displayed key in vitro biocontrol traits, such as the production of cell wall–degrading enzymes and siderophores. Greenhouse trials confirmed the efficacy of selected strains in controlling white mold and promoting bean plant growth. Isolates EVSA, BERA II, and BEFA I stood out by enabling the survival of plants inoculated with S. sclerotiorum while not impairing seed germination. Both bacterial co-inoculation (EVSA, BERA II, and BEFA I) and the EVSA strain alone promoted shoot and root development in bean plants. EVSA demonstrated multifunctional activity, combining effective suppression of S. sclerotiorum strain SSF with plant growth promotion, positioning it as a promising candidate for bioinoculant development in the sustainable management of white mold.

The critical role of temperature in ensuring reliable protective efficacy of a biocontrol agent targeting Sclerotinia sclerotiorum - M. Grimonpont; E. Turc; A. Lies; N. Monnier; P. C. Nicot; M. Bardin (BioControl, 2026)

Rachiplusia nu (Guenée) with field-evolved resistance to Bt soybean is susceptible to Bt-based biopesticides - Daniela Neves Godoy; Arthur Dallanora; Venicius Ernesto Pretto; Ramon Braida Palharini; Zanandra Zanini Tamiosso; Luiz Francisco Warpechowski; Oderlei Bernardi (BioControl, 2026)
Field-evolved resistance to the soybean event MON 87701 × MON 89788, which expresses the Cry1Ac toxin from Bacillus thuringiensis ( Bt ), was reported in Rachiplusia nu (Guenée) (Lepidoptera: Noctuidae) in Brazil and Argentina. Given this scenario, diet-overlay bioassays were conducted to assess the susceptibility of Brazilian populations of R. nu to the Bt -based insecticides DiPel WP and XenTari WG and to investigate potential cross-resistance with Cry1Ac using a laboratory-selected R. nu strain. Additionally, leaf bioassays were used to test the efficacy of field doses of these biopesticides against field-collected populations and laboratory-selected strains of R. nu. The LC 50 values of DiPel WP and XenTari WG for field populations of R. nu ranged from 0.03 to 0.09 and 0.46–0.60 μg active ingredient cm –2 of diet, respectively, representing resistance ratios ≤ 4.0-fold relative to a susceptible population. The Cry1Ac-resistant, Cry1Ac-susceptible and F 1 progeny of reciprocal crosses (heterozygotes) showed relatively similar susceptibility to DiPel WP and XenTari WG (resistance ratios ≤ 5.3-fold), indicating low but detectable cross resistance . Leaf bioassays demonstrated that field doses of DiPel WP and XenTari WG caused > 95% mortality in all populations and strains. These results indicate that Brazilian populations of R. nu remain susceptible to DiPel WP and XenTari WG, even after the evolution of resistance to Cry1Ac soybean and highlight these products as effective tools for controlling this polyphagous pest.

Compensatory feeding by lady beetles: enhanced biocontrol potential of Harmonia axyridis against caterpillars in salinity-affected agro-ecosystems - Sahil Pawar; Rorri Mueller; Bijay Subedi; Mahendra Pawar; Monica Kersch-Becker; Sara Hermann; Michelle Peiffer; Jared Ali; Gary W. Felton (BioControl, 2026)
The increasing salinization of agricultural land is a pressing problem, altering how plants interact with organisms across multiple trophic levels. While salinity-induced changes in plant chemistry are known to affect insect herbivores, it remains unclear how these changes shape predator responses. Here, we examined how prey quality (tomato fruitworm caterpillars— Helicoverpa zea ), shaped by soil salinity influences the foraging and consumptive behavior of the generalist predatory Asian lady beetle ( Harmonia axyridis ). We tested how salt stress in host plants (tomato – Solanum lycopersicum ) and "salty" H. zea caterpillars as prey shape predator attraction, feeding dynamics, and survival. Caterpillars reared on salt-treated artificial diets showed reduced protein content and slower growth. Despite this potentially lower prey quality, H. axyridis consumed more of the “salty” prey than the “non-salty” prey, suggesting a compensatory feeding response. Petri dish dual-choice assays showed no consistent preference for prey type during initial behavioral stages (touch, bite, consumption), but total intake was significantly higher for the “salty” caterpillars. In Y-tube olfactometer choice assays, predators were equally attracted to non salt-stressed and salt-stressed plants, indicating that salinity did not disrupt olfactory cue-mediated predator recruitment. Together, these results suggest that H. axyridis may adjust its feeding behavior to compensate for likely reduced prey quality and enhance biocontrol potential in salinity-affected systems.

Biocontrol characteristics and management potential of Paenibacillus polymyxa A818 against Fusarium head blight in wheat - Huijuan Peng; Yihua Liao; Tian Yang; Chao Liu; Xin Liu; Dongfang Ma; Chengcheng Li; Yujun Xing (BioControl, 2026)

The ability of predatory mites to cope with the woven nests of exotic bamboo spider mites - Naoki Matsumoto; Peter Schausberger; Yukie Sato (BioControl, 2026)

Harnessing rice endophytes for sustainable biocontrol of false smut fungus Ustilaginoidea virens (Cooke) Takahashi - Mathew Seikholen Baite; Letngam Touthang; Prabhukarthikeyan Seenichamy Rathinam; Raghu Shivappa; Keerthana Umapathy; Ch. Jamkhokai Mate (BioControl, 2026)

Evaluation of the banker plant system for an omnivorous mirid predator Nesidiocoris tenuis to control the whitefly Bemisia tabaci in greenhouses using numerical simulations - Yusuke Ikegawa; Eizi Yano (BioControl, 2026)

Fungal treatments do not compromise survival or fecundity of the pest, Anthonomus eugenii (Coleoptera: Curculionidae): implications for pest management - Jesús Ernesto Guerra-Sánchez; Esteban Rodríguez-Leyva; Manuel Alejandro Tejeda-Reyes; Ariel Wilbert Guzmán-Franco (BioControl, 2026)

Correction: Insecticidal activity of a Pseudomonas sp. isolated from cabbage root fly (Delia radicum L.) larvae exposed to D. radicum-suppressive soil - Max Wantulla; Marcel Dicke; Joop J. A. van Loon (BioControl, 2026)

Trichoderma inoculation alters the performance of Myzus persicae and enhances growth in Brassica rapa - Bilal Ahmad; Aleena Alam; Sohail Abbas; Yuexuan Li; Khalid Ali Khan; Hamed A. Ghramh; Jamin Ali; Qiyun Li; Rizhao Chen (BioControl, 2026)

RNAi-mediated suppression of OfRelish enhances the efficacy of entomopathogenic bacteria against Odontotermes formosanus (Blattodea: Termitidae) - Xinyi Tang; Kai Feng; Fang Tang (BioControl, 2026)

Environmental exposure alters the nutritional quality of honeydew for a parasitoid - Maite Fernández de Bobadilla; Anabel Millán-Leiva; Emanuele Porcu; Francesco Giovanni Filippello; Alejandro Tena (BioControl, 2026)

Revitalizing the lentil crop by use of a native Trichoderma sp. for Fusarium wilt and collar rot disease management and plant growth promotion - Sangam Choudhury; Sunita Mahapatra; Sunanda Chakraborty; Arup Sen; Sk. Hasibul Alam; Anubhab Hooi; B. Teja Bhushan (BioControl, 2026)

Tamarixia citricola Hansson and Guerrieri sp. nov. (Hymenoptera: Eulophidae): a new parasitoid of Diaphorina citri Kuwayamava (Hemiptera: Psyllidae) found during a classical biological control program in Cyprus - Alberto Urbaneja; Meritxell Pérez-Hedo; Nicos Seraphides; Anthemis Melifronidou-Pantelidou; Stalo Giallouridou; Lia Markou; Menelaos C. Stavrinides; Chrysos Kaponas; Omar Ruíz-Rivero; David J. W. Morgan; Christer Hansson; Mark S. Hoddle; et al. (BioControl, 2026)
Asian citrus psyllid, Diaphorina citri , is a major global pest because it is the primary vector of Candidatus Liberibacter spp., the causal agents of huanglongbing (HLB), a lethal citrus disease. Following the detection of D. citri in Cyprus in 2023, the first record of this pest in the European Union, a classical biological control program targeting this pest was initiated in spring 2024 using the parasitoid Tamarixia radiata imported from California, USA. During field surveys in summer 2024, parasitized D. citri nymphs were found both in release and non-release orchards. T. radiata was recovered from release sites, confirming its establishment. In contrast, parasitism in non-release orchards suggested the presence of native or unintentionally introduced parasitoids, or a rapid spread of T. radiata into new areas. To determine the identity of parasitoids associated with D. citri in Cyprus, an integrative approach was adopted combining field observations, molecular analyses of the COI gene, and morphological analyses. T. radiata recovered from Cyprus field sites matched reference sequences of parasitoids from California. However, other specimens were genetically and morphologically distinct and represented a new species. The new species is described here as Tamarixia citricola Hansson and Guerrieri sp. nov. Taxonomic diagnoses and characters for separating both Tamarixia species associated with D. citri are provided. Results presented here indicate the coexistence of both T. radiata (introduced) and T. citricola (likely autochthonous) in Cyprus citrus orchards. This finding has important implications for future biological control strategies and quarantine measures for D. citri in the Mediterranean basin.

Evaluation of the effectiveness of indigenous entomopathogenic fungi for controlling chilli thrips (Scirtothrips dorsalis Hood) in blueberry under greenhouse conditions - Hsin-Yu Lin; Yi-Ju Chen; Kusum Mushyakhwo; Chin-Mu Chen; Yu-Shin Nai (BioControl, 2026)

Insecticidal activity of a Pseudomonas sp. isolated from cabbage root fly (Delia radicum L.) larvae exposed to D. radicum-suppressive soil - Max Wantulla; Marcel Dicke; Joop J. A. van Loon (BioControl, 2026)

Limited establishment from widespread releases of the knotweed psyllid Aphalara itadori, a biological control agent for knotweeds in the USA - Fritzi S. Grevstad; Jeremy C. Andersen; Nancy C. Oderkirk; Jennifer Andreas; Lisa Tewksbury; Cynthia Detweiler; Joel Price; Bernd Blossey; Richard Reardon (BioControl, 2026)

Paraburkholderia oxyphila: a novel bacterial biocontrol species against the fungal plant pathogen Botrytis cinerea - Eudokia Kalfa; Eirini G. Poulaki; Vasilis Dimitrakas; Anastasia Venieraki; Sotirios E. Tjamos (BioControl, 2026)

Crimson clover improves biological control of Halyomorpha halys (Stål) by native stink bug egg parasitoids in pecan orchards - Emily B. Myers; P. Glynn Tillman; Ted E. Cottrell; Erin E. Grabarczyk (BioControl, 2026)

Biocontrol enemies have stronger effects than non-biocontrol enemies on insect prey - Peter Stiling; Marc J. Lajeunesse (BioControl, 2026)

Biocontrol potential of stem blight in macadamia by Bacillus spp. in plantlets with different scion-rootstock combinations - Marcos Giovane Pedroza de Abreu; Luana Laurindo de Melo; Vanessa Rafaela de Carvalho; Leonardo Massaharu Moriya; Bernardo de Almeida Halfeld-Vieira (BioControl, 2026)

Predation risks alter lysozyme levels and grooming behavior in Bactrocera dorsalis to affect entomopathogen success - Lu Xiao; Xianli Lu; Fengqin Cao; Xin Liu; Xingyu Geng; Lang Fu; Jian Wen (BioControl, 2026)

The ethics of using biocontrol: understanding public perceptions of, and attitudes towards, biocontrol in principle and dung beetles in particular - Bethaney Turner; Airong Zhang; Christina Maxwell; Valerie Caron (BioControl, 2026)
Biocontrol can be an effective tool in managing unwanted species and for environmental management. In-depth understanding of public perceptions and attitudes of biocontrol is critical to securing constructive public engagement in biocontrol initiatives. This study used mixed methods survey research with 155 Australian participants to identify key drivers of attitudes and perceptions and their associated impacts on acceptance of biocontrol. In addition, the study assesses if there were differences between public perceptions of, and attitudes towards, biocontrol in principle and the specific case of dung beetles introduced into Australia to mitigate issues arising from dung accumulation. The results indicate that while participants believe dung beetles are safer and more effective than biocontrol in principle, they consider them less necessary. Identification of biocontrol as an ethical approach to environmental management was the only shared driver of acceptance and positive attitude towards both biocontrol in general and dung beetles in particular. Positive perceptions of dung beetles were also motivated by identifying them as effective and useful. On the other hand, acceptance of biocontrol in principle was also driven by the perception that introducing an agent would pose limited threats to biodiversity, higher confidence in governance, and respondents being older. This study identifies the need for further research exploring the ethical positions of diverse publics to strengthen understanding of the factors driving acceptance or rejection of biocontrol in specific contexts. We conclude that a more nuanced and detailed approach to ethics could improve communication strategies, strengthen public-science trust and enhance scientific practices and outcomes.

Effects of an arbuscular mycorrhizal fungi on some biological characteristics of Myzus persicae (Sulzer) (Hemiptera: Aphididae) - Gizem Berber Tortop; Hülya Özgönen Özkaya; Ali Kemal Birgücü (BioControl, 2026)

Biocontrol potential of beauvericin produced in a submerged culture of Beauveria bassiana 331R against cotton aphid Aphis gossypii - Jong-Cheol Kim; In Min Hwang; Ho Myeong Kim; Seulbi Kim; Hyunbok Song; Seulki Kim; Tae Young Shin; Taek Su Shin; Soo‑Dong Woo; Hae Woong Park (BioControl, 2026)

Isolation of Leptolegnia chapmanii, an entomopathogenic oomycete, from Misiones, Argentina: a promising tool for vector mosquito control - Manuel E. Rueda-Páramo; Christina Schuster; Dario Balcazar; Flavia V. Diez del Valle; Alejandra C. Gutierrez; Anna Heitmann; Oscar D. Salomon; Andreas Leclerque (BioControl, 2026)

Synergistic effects of nucleopolyhedroviruses on larvicidal activity against Spodoptera litura and Helicoverpa armigera - Zihan Shi; Jing Li; Can Wang; Shaolong Wu; Wei-ai Zeng; Shiping Jia; Yusheng Wang; Yansong Xiao; Mi Li; Lin Tan (BioControl, 2026)

Haunted by cane toads—An exploratory survey of public attitudes and knowledge about classical biological control - Chris Looney; Jennifer Andreas; Shannon M. Donovan (BioControl, 2026)

Parasitoid releases to manage Queensland fruit fly, Bactrocera tryoni, in southeastern Australia - Lucy K. R. McLay; Joanne C. Dawson; J. Paul Cunningham (BioControl, 2026)
Queensland fruit fly, Bactrocera tryoni (Froggatt) (Diptera: Tephritidae), is Australia’s most economically important horticultural pest. Its range has expanded from its ancestral habitat in rainforests of northeastern Australia into southeastern Australia, and commercial crops. Biocontrol using parasitoid wasps has considerable potential in assisting the area-wide management of B. tryoni in southeastern Australia where they are largely absent. We mass-reared and released two species of parasitoid wasp, Fopius arisanus (Sonan) (Hymenoptera: Braconidae) and Diachasmimorpha kraussii (Fullaway) (Hymenoptera: Braconidae), at six locations in southeastern Australia where they were previously absent. Parasitoid persistence and establishment were monitored over three growing seasons through field collection of B. tryoni infested fruit. Both species parasitised B. tryoni in the field and persisted at the release sites within season. Parasitism rates were up to 63% for D. kraussii and 38% for F. arisanus . D. kraussii were recovered at two of four monitored sites a year after the last releases, indicating the potential of this species to establish in southeastern Australia. In a second study we performed choice and no-choice laboratory experiments to determine if either parasitoid species could target and parasitise the tephritid, Urophora stylata (F.) (Diptera: Tephritidae), which is an established classical biocontrol agent for weed thistles. We found no evidence that either parasitoid can parasitise U. stylata . Our studies indicate that F. arisanus and D. kraussii have potential as biocontrol agents as part of integrated pest management and area-wide management for B. tryoni in southern Australia, with D. kraussii as the more promising candidate.

Antagonistic activity and genomic insights of leaf-endophytic bacteria as biocontrol agents against major Brassica pathogens - Micaela Ester Stieben; Franco Rubén Rossi; Leandro Solmi; Andrés Gárriz; Oscar Adolfo Ruiz; Fernando Matías Romero (BioControl, 2026)

An indigenous Metarhizium sp. strain amended in compost enhances sweetpotato growing system and management of Cylas formicarius (Coleoptera: Curculionidae) - Landon Gee Keong Wong; Koon-Hui Wang; Roxana Myers; Brent S. Sipes (BioControl, 2026)